ANALISIS PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. ADIRA DINAMIKA MULTIFINANCE PONTIANAK - B31111032, Septia Indah Nelviani (Jurnal Manajemen Update, 2016)
The research was conducted at SMA Muhammadiyah 1 Pontianak, using situational leadership and job motivation as the independent variables, and performance as the dependent variable. This research aimed to evaluate and analyze the influences of situational leadership on the performance of the teachers at SMA Muhammadiyah 1 Pontianak, and the influences of job motivation on the performance teachers at SMA Muhammadiyah 1 Pontianak. The population in this research included 54 teachers at SMA Muhammadiyah 1 Pontianak. The sources of data were both primary data and secondary data. The primary data were collected through interviews and questionnaires distributed to a sample/respondents of the research. The secondary data were collected from the documentation and literature reviews, and research related to the research materials.SPSS version 16,00 was used as a tool to analyze the data. This research used a desciptive and causal method.The techniques used to test the data in the research included validity test, reliability test, classic assumption test and double linear regression analysis. The research findings indicated that situational leadership and job motivation had a positive and significant influence on the performance of the teachers at SMA Muhammadiyah 1 Pontianak, with an influence of 314,037. Situational leadership had a positive and significant influence on the teachers performance, with an influence of 2,288. Job motivation had a positive and significant influence on the teachers performance, with an influence of 8,124.Based on the findings it can be concluded that the situational leadership and job motivation contributed significantly to the performance of teachers at SMA Muhammadiyah 1 Pontianak. Keywords : Situational leadership, job motivation and performance.